SemMedDB: a PubMed-scale repository of biomedical semantic predications - Kilicoglu, Halil; Shin, Dongwook; Fiszman, Marcelo; Rosemblat, Graciela; Rindflesch, Thomas C. (Bioinformatics, 2012)
Effective access to the vast biomedical knowledge present in the scientific literature is challenging. Semantic relations are increasingly used in knowledge management applications supporting biomedical research to help address this challenge. We describe SemMedDB, a repository of semantic predications (subject–predicate–object triples) extracted from the entire set of PubMed citations. We propose the repository as a knowledge resource that can assist in hypothesis generation and literature-based discovery in biomedicine as well as in clinical decision-making support. Availability and implementation: The SemMedDB repository is available as a MySQL database for non-commercial use at http://skr3.nlm.nih.gov/SemMedDB. An UMLS Metathesaurus license is required. Contact:  kilicogluh@mail.nih.gov